Vocational teachers’ experiences of using an online learning platform - Wong, Bo Man (2018)
Much research has been carried out to demonstrate how the online platforms can be used to improve teaching and learning processes. However, they have been less explored in relation to vocational education, where the situation is often more complex and the possible solution options tend to be more constrained than in the contexts where these online technologies have been created.